Budaya Pop dan Politik: Analisis Semiotik terhadap Penampilan Iwan Fals di TRANS TV, 4 April 2004 - Pawito . (FISIP Universitas Atma Jaya Yogyakarta, 2005)
Abstract: This reseach is aimed at examinig the meaning of Iwan Falsâ€™ live music concert broadcasted by TRANS TV, 4 April 2004. The method of Semiotic Analysis is deployed scrutinizing the live concert. The concert was seen as an integrated text comprising a set of signs amplified by television. The reseach shows that the concert was fullyÂ loaded with moral values with regard to, primarily, power, politics, corruption, and performance of parliament members (DPR). The ideology of resistance was found significantly in the concert.